# (7m^8-5m^3+9m^2+5)+(9m^7+3m^3-4m)=

## Simple and best practice solution for (7m^8-5m^3+9m^2+5)+(9m^7+3m^3-4m)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for (7m^8-5m^3+9m^2+5)+(9m^7+3m^3-4m)= equation:

Simplifying
(7m8 + -5m3 + 9m2 + 5) + (9m7 + 3m3 + -4m) = 0

Reorder the terms:
(5 + 9m2 + -5m3 + 7m8) + (9m7 + 3m3 + -4m) = 0

Remove parenthesis around (5 + 9m2 + -5m3 + 7m8)
5 + 9m2 + -5m3 + 7m8 + (9m7 + 3m3 + -4m) = 0

Reorder the terms:
5 + 9m2 + -5m3 + 7m8 + (-4m + 3m3 + 9m7) = 0

Remove parenthesis around (-4m + 3m3 + 9m7)
5 + 9m2 + -5m3 + 7m8 + -4m + 3m3 + 9m7 = 0

Reorder the terms:
5 + -4m + 9m2 + -5m3 + 3m3 + 9m7 + 7m8 = 0

Combine like terms: -5m3 + 3m3 = -2m3
5 + -4m + 9m2 + -2m3 + 9m7 + 7m8 = 0

Solving
5 + -4m + 9m2 + -2m3 + 9m7 + 7m8 = 0

Solving for variable 'm'.

The solution to this equation could not be determined.`